2021
DOI: 10.1002/adfm.202011146
|View full text |Cite
|
Sign up to set email alerts
|

Pore Tuning of Metal‐Organic Framework Membrane Anchored on Graphene‐Oxide Nanoribbon

Abstract: Although the pore structures and gas transport properties of metal‐organic frameworks (MOFs) have been tuned mainly by modifying the framework building blocks, a pore‐tuned zeolitic imidazolate framework (ZIF)‐8 layer is directly grown on graphene oxide nanoribbons (GONR)‐treated polymer substrate. Oxygen‐containing functional groups and GONR dangling‐carbon bonds facilitated the spontaneous growth of ZIF‐8 oriented to the (100) grain on the GONR surface and also enhanced the rigidity by strongly anchoring the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 68 publications
1
33
0
Order By: Relevance
“…Figure 3D is a model representation depicting the influence of the ZIF-8 fillers on the transport pathway of the 6FDA-DAM polymeric membrane. The sieving properties of ZIF-8 arise because of the varying transport resistance of the gases, where fast-passage propylene molecules are permitted through the crystals, while propane permeation is hindered because of the 4 Å aperture size, which is smaller than the kinetic diameter of propane (4.3 Å) ( 24 , 51 , 52 ). Therefore, ZIF-8–containing MMMs show better separation performance than pristine 6FDA-DAM membranes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 3D is a model representation depicting the influence of the ZIF-8 fillers on the transport pathway of the 6FDA-DAM polymeric membrane. The sieving properties of ZIF-8 arise because of the varying transport resistance of the gases, where fast-passage propylene molecules are permitted through the crystals, while propane permeation is hindered because of the 4 Å aperture size, which is smaller than the kinetic diameter of propane (4.3 Å) ( 24 , 51 , 52 ). Therefore, ZIF-8–containing MMMs show better separation performance than pristine 6FDA-DAM membranes.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1A provides a schematic of ZIF-8 nanoplate synthesis. Among the various MOF crystals, ZIF-8 was selected owing to its effective aperture size of approximately 4 Å, which is ideal for separating propylene/propane molecules and is the most widely studied MOF for gas separation (24)(25)(26). The ZIF-8 nanoplates are developed by first synthesizing a high-aspect ratio Zn template in the form of Zn 5 (NO 3 ) 2 (OH) 8 .…”
Section: Synthesis Of Zif-8 Nanoplate Via Conversion Methodsmentioning
confidence: 99%
“…Based upon data from synchrotron X-ray scattering, density-functional theory (DFT) and molecular dynamics simulations, and other techniques, it is generally accepted that ZIF formation involves a sequence of events starting from the formation of small (~1 nm) metastable prenucleation clusters, which evolve through aggregation followed by intraaggregate ZIF nucleation and growth. Recent studies on surface-directed MOF growth [38][39][40][41][42][43][44][45][46] indicate that the diffusion of MOF precursors in the vicinity of the 2D material, and the MOF-2D material interactions, are key to regulate the crystallinity of the MOF film and the ability to maintain in-plane/horizontal growth (desired for ultrathin films) versus out-of-plane/vertical (undesired) growth.…”
Section: Main Textmentioning
confidence: 99%
“…The key component of an electrochemical sensor is the electrode material, so this material must be carefully designed to achieve enhanced sensing performance. In this context, it has been previously reported that electrode materials possessing large surface areas, abundant active sites, and specific responses toward HMIs are of particular interest. From this perspective, the emergence of metal–organic frameworks (MOFs), which are assembled with structure-directing organic ligands and metal centers, has received attention for the preparation of promising electrode materials because of their open metal sites, tunable structures, and large surface areas. Thiacalix[4]­arene-based derivatives, which possess large inner cavities and functionalized upper and lower edges, are good organic ligands for use in the preparation of metal–organic assemblies. In these systems, the introduced functional groups, such as −SH, −NH 2 , and −COOH groups, can interact with HMIs using Lewis acid–base attractions. Furthermore, thiacalix[4]­arene-based complexes contain abundant phenyl rings, which promote binding to HMIs through cation···π interactions. In addition, their self-assembled pore structures can accelerate the adsorption response toward HMIs, which is beneficial for the preconcentration process of HMIs. , For instance, Wang et al designed a new sulfur-containing MOF sensor that was formed by the self-assembly of calix[4]­resorcinarenes, Co­(II) cations, and 1,4-benzenedicarboxylic acid, and this sensor exhibited an excellent capture and detection performance toward HMIs .…”
Section: Introductionmentioning
confidence: 99%